Analysis of the Utilization of Gotong Royong Board Media to Develop Communication Skills of Grade 1 Elementary School Students - Khanifah, Rizka Nur; Saputro, Bagus Ardi; Setyaningsih, Dwi; Nuroso, Harto (DIDAKTIKA, 2024)
Mutual cooperation board media or pagorong for short is a medium offered to improve student understanding and invite students to play an active role in discussing material. In this way, this mutual cooperation board media is suitable for use in the learning process in developing student communication. In line with this research which aims to develop the communication skills of lower class students through the medium of mutual cooperation boards. This research used a qualitative descriptive method which was carried out at SD Negeri di Kota Semarang in class 1B. In collecting data, this research used interviews, observation, questionnaires and documentation, then analyzed to find results. The results of this research show that each communication indicator gets a very good category, with details of enthusiasm of 94%, capability of 100%, credibility of 86%, symphaty of 93%, and clarity of 100%. With this, class 1B students at SD Negeri di Kota Semarang have high courage and enthusiasm in learning using the mutual cooperation board media. This will of course have an impact on developing communication skills in conveying ideas, asking questions and providing answers, increasing students' enthusiasm and thinking abilities, so that students can connect and construct the knowledge and experiences they have.